Adaptive radiotherapy for advanced lung cancer ensures target coverage and decreases lung dose - Møller, Ditte Sloth; Alber, Markus (Radiotherapy and oncology, 2016)
Advanced lung cancer patients experience anatomical changes during radiotherapy. Uncorrected, these may lead to lower tumor dose, but can be corrected for by adaptive radiotherapy (ART). Anatomical changes in 233 patients were monitored online on cone-beam CT-scans used for daily soft-tissue matching. If systematic changes above the pre-defined trigger criteria were observed, a new CT-scan, delineations, and treatment plan were made, restoring the intended dose distribution. Dose distributions with and without adaptation were compared. The first fifty ART patients were given two surveillance CT-scans during radiotherapy. These were used to evaluate delivered dose for patients without adaptation. The first fifty-two patients treated with ART were also compared with 52 pre-ART patients to evaluate the reduction in normal tissue doses. Sixty-three patients (27%) were adapted. Seventy-five per cent of all adaptations correctly adjusted for a decrease in tumor dose. Eighty-seven surveillance CT-scans were obtained for the first fifty patients and in only 2% of the cases, a decrease in tumor coverage (ΔV95%CTV>1%) was observed. With ART we observed a significant decrease in lung dose (MLD reduced from 14.6Gy to 12.6Gy on average). Implementation of soft-tissue match combined with ART decreased the lung dose. The trigger criteria used correctly identified all but one (98%) of the patients requiring adaptation with a false positive rate of 20%.